Study of the short-term quality of life of patients with esophageal cancer after inflatable videoassisted mediastinoscopic transhiatal esophagectomy - Wang, Gaoxiang; Sun, Xiaohui; Li, Tian; Xu, Meiqing; Guo, Mingfa; Liu, Changqing; Xie, Mingran (Frontiers in Surgery, 2023)
Objective: To compare the short-term outcomes and postoperative quality of life in patients with esophageal cancer between inflatable videoasisted mediastinoscopic transhiatal esophagectomy(IVMTE) and minimally invasive Mckeown esophagectomy(MIME), and to evaluate the value of IVMTE in the surgical treatment of esophageal cancer. Methods: A prospective, nonrandomized study was adopted. A total of 60 esophageal cancer patients after IVMTE and MIME December 2019 to January 2022 were included. Among them, 30 patients underwent IVMTE and 30 patients underwent MIME. Shortterm outcomes (including the operation time, intraoperative blood loss, postoperative drainage 3 days, total postoperative tube time, postoperative hospital stay, number and number of thoracic lymph node dissection stations, postoperative complications and so on), postoperative quality of life, [including Quality of Life Core Questionnaire (QLQ-C30) and the esophageal site-specific module (QLQ-OES18)]were compared between the 2 groups. Results: The operation time, intraoperative blood loss, postoperative drainage volume and total postoperative intubation time in IVMTE group were significantly lower than those in MIME group (P < 0.05). A total of 22 patients had postoperative complications, including 7 patients in IVMTE group (23.3%) and 15 patients in MIME group (50.0%). There was significant difference between the two groups (P=0.032). The physical function, role function, cognitive function, emotional function and social function and the overall health status in the IVMTE group were higher than those in the MIME group at all time points after operation, while the areas of fatigue, nausea, vomiting and pain symptoms in the MIME group were lower than those in the MIME group at all time points after operation. Conclusion: IVMTE is a feasible and safe alternative to MIME. Therefore, when the case is appropriate, IVMTE should be given priority, which is conducive to postoperative recovery and improve the quality of life of patients after operation.